1998
DOI: 10.1111/j.1440-1746.1998.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Helicobacter pylori eradication with 2 week combination therapy of lansoprazole and amoxycillin: Intragastric distribution of colonization and gastric mucosal atrophy

Abstract: In Japan, gastric ulcers are often accompanied by marked gastric mucosal atrophy. We evaluated the dual therapy of double-dose lansoprazole and amoxycillin for Helicobacter pylori eradication in Japanese ulcer patients and investigated the effects of intragastric distribution of H. pylori colonization and gastric mucosal atrophy on eradication with this combination therapy. Seventy-six H. pylori-positive ulcer patients received lansoprazole (30 mg) plus amoxycillin (500 mg) twice daily for 2 weeks (LA-60 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…By screening references listed in the remaining 67 articles and relevant reviews, an additional 12 articles were found. After reviewing the 79 full texts, 20 articles fulfilled the inclusion criteria (Figure 1) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By screening references listed in the remaining 67 articles and relevant reviews, an additional 12 articles were found. After reviewing the 79 full texts, 20 articles fulfilled the inclusion criteria (Figure 1) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Search Resultsmentioning
confidence: 99%
“…One reported that atrophy decreased after H. pylori eradication [33]. The other only followed-up for 8 weeks, and did not report the different effects between treatment and control groups [32].…”
Section: Special Reportmentioning
confidence: 97%
See 2 more Smart Citations
“…A total of 73 studies (57 papers and 16 abstracts) were included in this systematic overview. 10–82 Of those, 60 were randomized controlled trials. The study design was unclear or unstated in 13 reports.…”
Section: Resultsmentioning
confidence: 99%